CORRELATION BETWEEN VOCABULARY MASTERY AND SPEAKING ABILITY OF UNDERGRADUATE STUDENTS AT TADULAKO UNIVERSITY - Roland, Roland; Darmawan, Darmawan; Budi, Budi (Tadulako University, 2025)
This research aims to find out correlation between vocabulary mastery and speaking ability of undergraduate students at Tadulako University. The subjects of this research were students of the fourth semester and the research subjects were randomly selected to be the sample of this study. The total number of samples was 30 students. They worked on a test of vocabulary and speaking to have data of the relationship. The data were tested to have normality and linear relationship and the result of tests indicated that data are normally distributed and have a linear relationship. Then, the data were analyzed using Pearson Product Moment Correlation Coefficient to find out the correlation between vocabulary mastery and speaking ability. The result of analysis indicated that the correlation coefficient between vocabulary mastery and speaking ability is 0.559. The result is categorized as “moderate” (0.40 to 0.59). Therefore, the hypothesis of the study is accepted, in which there is a positive correlation between vocabulary mastery and speaking ability of the eight grade students. In other word, the greater the English vocabulary student acquire, the better their speaking ability is.